Bank stability and toe erosion model of the Kodku Khola bank, southeast Kathmandu valley, central Nepal - Thapa, Ishwor; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2016)
The Kodku Khola is a potential river from the southeast part of Kathmandu valley as it has been used for irrigation and household purposes from prehistoric time. The river is suffering from streambank instability causing great threat to the infrastructure, land and settlement areas. In this context, assessment of Bank Stability and Toe Erosion Model (BSTEM) of the Kodku Khola was undertaken for eight different sites using the BSTEM version 5.4 that calculates a Factor of Safety (Fs) for multilayer streambank, based on limit equilibrium-method. Streambank of the uppermost reach around the transects BK1 (Lower Badikhel) and BK2 (Upper Taukhel) area is stable, where Fs exceeds 1.3 and maximum lateral retreat of channel is 21.86-30.59 cm with 0.025-0.290 m2 of the total eroded area of the bank-toe resulting in less bank toe erosion. Canopy and understorey cover with consolidated bank materials are the causes of stable banks. Streambank of transects BK3 (Arubot) and BK4 (Thaiba) are unstable as Fs ranges from 0.75 to 0.92, and the maximum lateral retreat of channel ranges 70.83-208.81 cm with total eroded bank toe area of 0.117–1.695 m2 resulting in excessive bank toe erosion problems. Major causes of instability are the presence of unconsolidated bank material, high scouring, and sparse riparian vegetation. Within the transects BK6 and BK7 around Harisiddhi, streambanks are stable with less bank toe erosion hazard because of channelization. Where the Fs are low and banks are disturbed by encroachment, suitable bioengineering measures can be implemented to mitigate excessive bank toe erosion and failure.